TINGKAH LAKU MAKAN ELANG LAUT PERUT PUTIH (Haliaeetus leucogaster) DI PUSAT PENYELAMATAN SATWA TASIK OKI SULAWESI UTARA - Loindong, Andrew; Kiroh, H. J.; Wahyuni, I; Saerang, J. L.P. (ZOOTEC, 2016)
INGESTING BEHAVIOUR OF WHITE BELLIED SEA EAGLE (Haliaeetus leucogaster) IN TASIKOKI CENTRAL WILD ANIMAL RESCUE IN MINAHASA UTARA. This study aimed to describe the ingesting of white bellied sea eagle (Halliaetus leucogaster) in Tasikoki Central Wild Animal Rescue on safeguarding cage as one of the conservation strategy for translocation purpose. The expected benefits was to provide information about ingesting behavior of white bellied sea eagle and the reference knowledge information in the field of wild life conservation measures. This research was conducted using observational methods and instantaneous animal sampling technique of 14 animal samples. Study began at 07.00 am until 17.00 pm. The variables observed is observing prey, catching prey and ingesting prey of white bellied sea eagle as the variables of this study. The observing result is showed that white bellied sea eagle was ingesting fish and other eagle (cannibal animal). The ingesting behavior was affected by the kind of prey, which one of the favorite prey of white bellied sea eagle. The other eagle and the agonistic behavior mostly happened when they prey the other eagle. White bellied sea eagle observed the prey and other thing around the cage with the percentage of 3%. White bellied sea eagle only catches fish with a percentage of 1%. White bellied sea eagle was ingesting prey with a percentage of 96%. The animal was very sensitive in ingesting fish more than ingesting other eagle. Keywords : White bellied sea eagle (Halliaetus leucogaster), Ingesting Behavior, Tasikoki Central Wild Animal Rescue Tasikoki.